230k views
3 votes
Solve the equation. 3(x+4)+2=2+5(x-4)

User EpokK
by
7.5k points

2 Answers

6 votes

Answer:

Explanation:

To solve the equation 3(x + 4) + 2 = 2 + 5(x - 4), we need to isolate the variable x on one side of the equation. Here's how we can do it:

Expand the left side of the equation:

3(x + 4) + 2 = 2 + 5(x - 4)

3x + 12 + 2 = 2 + 5x - 20

3x + 14 = 5x - 18

Subtract 3x from both sides:

3x + 14 = 5x - 18

0 = 2x - 4

Add 4 to both sides:

0 + 4 = 2x - 4 + 4

4 = 2x

Finally, divide both sides by 2:

4 / 2 = 2x / 2

2 = x

So the solution to the equation is x = 2.

User Atsby
by
7.8k points
4 votes
x=16

3(x+4)+2=2+5(x-4)
Distribute: 3x+12+2=2+5x-20
Condense (simplify like terms): 3x+14=5x-18
-2x=-32
x=16

Hope this helps! If you find my answer helpful, please consider marking brianliest! If you have any questions, feel free to ask in the comments!
User Renan Basso
by
8.0k points